2015
DOI: 10.18178/ijtef.2015.6.6.485
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Analysis on the Factors of Alleviating Poverty among Women Entrepreneurs

Abstract: Abstract-In the recent years, the influx of women in business continues to record poor performance in combating the poverty. Poverty is rampant and become main issue in developing countries, as it will improve the socioeconomic of the countries. The objective of this research is to find out the contributing factors in alleviating poverty for women entrepreneurship. A total of 196 samples were collected from women entrepreneurship in Terengganu and Kelantan. Data analysis was conducted using SPSS 20.0. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Their study categorized the amount of loan borrowed, age, gender, educational level, assets owned before joining the microcredit programme, person in charge who handled the programme and area of residence as the important factors contributing to the level of income by the microcredit recipients. Hussin et al (2015) evaluated five factors that contribute the sustainability of micro-enterprise which are personality factor, cultural factor, environment factor, microfinance factor and entrepreneurial factor. The result of the study argued that selfconfidence, presence of role model, marketing opportunity, saving method, and communication skills are critical factors that increase the economic performance of the micro-enterprise.…”
Section: Factors Contributing To the Sustainability Of Micro-enterprisementioning
confidence: 99%
“…Their study categorized the amount of loan borrowed, age, gender, educational level, assets owned before joining the microcredit programme, person in charge who handled the programme and area of residence as the important factors contributing to the level of income by the microcredit recipients. Hussin et al (2015) evaluated five factors that contribute the sustainability of micro-enterprise which are personality factor, cultural factor, environment factor, microfinance factor and entrepreneurial factor. The result of the study argued that selfconfidence, presence of role model, marketing opportunity, saving method, and communication skills are critical factors that increase the economic performance of the micro-enterprise.…”
Section: Factors Contributing To the Sustainability Of Micro-enterprisementioning
confidence: 99%
“…Saad (2010) indicated that the microcredit and training activities provided by microfinance has lessen poverty and enhanced health status of beneficiaries. Hussin, Munir, Aziz, Muhamad, and Yaacob (2015) stated that the incorporation of entrepreneurial trainings and microcredit services assist micro‐ and small enterprises. Samer, Majid, Rizal, Muhamad, and Rashid (2015) showed that microcredit and training have positive impacts on their income and welfare status.…”
Section: Literature Reviewmentioning
confidence: 99%